Evaluación de las máquinas y herramientas del laboratorio de industrial de la Universidad Técnica Estatal de Quevedo - Moreta Vaca, Raúl Alexander (2022)
This research paper details the evaluation carried out on the machines and tools of the Industrial Laboratory at the State Technical University of Quevedo, and analyzed the current state of each machine / tool in the following laboratories: Mechanics Laboratory, Network Laboratory, Basic Sciences Laboratory and Materials Laboratory. In order to determine the state of each physical asset, field research was used at the corresponding study site, in order to diagnose the shortcomings, breakdowns, failures of each asset and propose improvement solutions for a better operability of each machine / tool in order to extend the useful life of each machine and improve the availability of these so that students can carry out the respective practices. To analyze each component of the machines / tools of the various laboratories, different maintenance methodologies were used such as: Criticality Analysis, which is a tool that assigns a criticality weighting to each asset depending on its potential risks that could affect the operability of each machine / tool in order to prioritize its activities and maintenance frequencies, Failure Mode and Effect Analysis (AMEF) was also used, a method that allows analyzing how a failure is generated and its corresponding effects all in order to determine actions that reduce the frequency of these failures. Through the different maintenance methodologies used and the corresponding diagnosis, some machines, tools and instruments of the Mechanics Laboratory and Basic Sciences Laboratory were repowered, service activities were carried out in the Materials and Networks laboratories, because these assets do not present serious failures. After analyzing the failures of each physical asset in the four laboratories, a maintenance plan is proposed, in order to improve the conditions of conservation and care of the same, in turn a distribution proposal is made for the machines and tools of the Mechanics and Materials laboratories. Keywords: Current status, criticality, maintenance, severity, occurrence, failures.